Extended-spectrum β-lactamase-producing Enterobacterales in diverse foodstuffs: a prospective, longitudinal study in the city of Basel, Switzerland - Gómez-Sanz, Elena; Bagutti, Claudia; García-Martín, Ana B.; Roth, Jan A.; Alt Hug, Monica; Maurer Pekerman, Laura; Schindler, Ruth; Furger, Reto; Eichenberger, Lucas; Steffen, Ingrid; Hübner, Philipp; Stadler, Tanja; et al. (Frontiers in Microbiology, 2023)
Background The involvement of non-human-to-human transmission of extended-spectrum β-lactamase-producing Enterobacterales (ESBL-PE) remains elusive. Foodstuffs may serve as reservoirs for ESBL-PE and contribute to their spread. Aim We aimed to systematically investigate the presence and spatiotemporal distribution of ESBL-PE in diverse unprocessed foodstuffs of different origin purchased in a central European city. Methods Chicken and green (herbs, salad, sprouts, vegetables) samples were collected monthly for two consecutive years, from June 2017 to June 2019, from large supermarket chains and small local food retailers, representing all ten postcode areas of the City of Basel (Switzerland), and the kitchen of the University Hospital Basel (Basel, Switzerland). After enrichment, presumptive ESBL-PE were isolated by selective culture methods and identified by Matrix-assisted laser desorption/ionization time-of-flight mass spectrometry. ESBL production was confirmed by phenotypic testing. Results Among 947 food samples, 14.8% were positive for ESBL-PE isolate/s belonging to eight different ESBL-producing bacterial species. Escherichia coli and Serratia fonticola were predominant across samples (9 and 2%, respectively). Higher ESBL-PE prevalence was observed in chicken (25.9%) than in green (3.8%) samples (p < 0.001). Among greens, ESBL-PE were most frequently isolated from sprouts (15.2%). High ESBL-PE species diversity was observed among chicken samples, with E. coli as predominant (17.6%). ESBL-producing Enterobacter cloacae was detected among different greens. Yet, ESBL-producing Klebsiella pneumoniae was predominant in sprouts (12.1%). In total, 20.5% of samples from organic farming and 14.2% of samples from conventionally raised animals harbored an ESBL-producing isolate. Detection of ESBL-PE across samples differed between organic and non-organic when stratified by food source (p < 0.001), particularly among greens (12.5% organic, 2.4% conventional). High proportion of organic chicken samples was positive for ESBL-E. coli (33.3%), while the detection of several species characterized the conventional chicken samples. No significant differences in ESBL-PE frequences were detected between national (13.4%) and international samples (8.0%) (p = 0.122). Instead, differences were observed between regions of food production and countries (p < 0.001). No significant differences were found when comparing the proportion of ESBL-PE positive samples across districts, shop sizes and the hospital kitchen. The percentage of ESBL-PE positive samples did not differ monthly across the two-year sampling period (p = 0.107). Conclusion Our findings indicate moderate dissemination of ESBL-PE in foodstuffs, especially between chicken products and sprouts. Chicken meat represents a source for several ESBL-producing Enterobacterales, especially E. coli, while greens are more prone to carry ESBL-K. pneumoniae and E. cloacae. We disclose the importance of food type, food production system and production origin when assessing the risk of contamination with different ESBL-PE species.